Desenvolvimento de membranas nanocompósitas para aplicação em processos osmóticos - Ohland, Anderson Luis (2019)
In this work, high-performance membranes were developed for application in osmotic processes. Reverse osmosis (RO) stands out as a technology for water desalination, while forward osmosis (FO) is an alternative to generate renewable energy. Two were the membrane synthesis methods studied: phase inversion (PhI) and interfacial polymerization (IP). In both methods, inorganic hydroxyapatite (Hap) particles were added to evaluate the effect of the incorporation of this material on the membrane transport properties. Prior to the incorporation, however, the particles underwent a plasma treatment in order to increase their hydrophilicity. The results showed that the incorporation of the functionalized Hap in the membranes synthesized by PhI increased the hydraulic permeability in RO by 30% and the water flux in FO by 60%, keeping the selectivity constant. Membranes synthesized by IP achieved increases of 70% and 65% in RO and FO, respectively, with incorporation of particles in the selective layer and in the porous substrate, whithout affecting the selectivity. This thesis indicates the potential of plasma application in particle surface treatment and an advancement of the transport mechanisms of nanocomposite membranes for osmotic processes.